Government Efforts to Resolve the Warri Crisis of 1997 a 2004 (Global Journal of Human-Social Science, 2017)
Many people (including non Nigerians) are aware that there was a serious crisis between the Ijo and Itsekiri of the Warri area of the Western Niger Delta region of Nigeria. Some of these people may also be aware that the crisis was caused mainly by the relocation of the headquarters of the then newly created Warri South (later Warri South-West) Local Government Area from Ogbe-Ijoh, an Ijo town, to Ogidigben, an Itsekiri town, by the General SaniAbacha -led Federal Military Government of the time. What many may not be aware of, is how the crisis was resolved. This article examines the efforts made by the Delta State and Federal Governments of Nigeria to end the crisis.